Genomic insights into Neolithic founding paternal lineages around the Qinghai-Xizang Plateau using integrated YanHuang resource - Mengge Wang; Yunhui Liu; Lintao Luo; Yuhang Feng; Zhiyong Wang; Ting Yang; Huijun Yuan; Chao Liu; Guanglin He (iScience, 2024)
Summary: Indigenous populations of the Qinghai-Xizang Plateau exhibit unique high-altitude adaptations, especially within Tibeto–Burman (TB) groups. However, the paternal genetic heritage of eastern Plateau regions remains less explored. We present one integrative Y chromosome dataset of 9,901 modern and ancient individuals, including whole Y chromosome sequences from 1,297 individuals and extensive Y-SNP/STR genotype data. We reveal the Paleolithic common origin and following divergence of Qinghai-Xizang Plateau ancestors from East Asian lowlands, marked by subsequent isolation and Holocene expansion involving local hunter-gatherers and millet-farming communities. We identified two key TB-related founding lineages, D-Z31591 and O-CTS4658, which underwent significant expansions around 5,000 years ago on the Qinghai-Xizang Plateau and its eastern Tibetan-Yi Corridor. The genetic legacy of these TB lineages highlights crucial migration pathways linking the Plateau and lowland southwestern China. Our findings align paternal genetic structures with East Asian geography and linguistic groups, underscoring the utility of Y chromosome analyses in unraveling complex paternal histories.